Manifesto: Contemporary Housing. An Interpretation of the Bauhaus Idea (EAAE Annual Conference Proceedings, 2023)
Housing needs change depending on the social situation, financial and technological potentials, the availability of functional solutions, and aesthetic expectations. An apartment is more than a building or part of it. This is the space where the Home is being built.